Comparison Of Saw And Wp Method Through A Sensitivity Test Approach In Employee Performance Assessment At PT. Port Of Indonesia II (PERSERO) Bengkulu Branch - Pramadana, Yoga; Sari , Herlina Latipa; Sartika , Devi (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
So far, the performance appraisal process at PT. Pelabuhan Indonesia II (Persero) Bengkulu Branch has utilized the Excel office application to provide values and calculate the final results of the employee's performance appraisal. However, this is an obstacle for PT. Pelabuhan Indonesia II (Persero) Bengkulu Branch, because it takes quite a lot of time to input employee data one by one in Microsoft Excel and provide performance values for each employee. In addition, there are frequent data input errors, which cause errors in giving the final value of employees and there is also an inaccurate rating for employees, which results in the final value obtained by each employee is not as it should be. The employee performance appraisal application was built to find out the results of the comparison between the SAW and WP methods through a sensitivity test approach in evaluating employee performance at PT. Pelabuhan Indonesia II (Persero) Bengkulu Branch. In addition, this application can be used as an alternative in knowing the results of employee performance appraisals based on the SAW and WP methods. Based on the results of the sensitivity test on the SAW and WP methods, it shows that the SAW method has a total change of 0%, the WP method is 0.000256%. Thus, it can be concluded that the WP method is considered relevant in solving problems in employee performance appraisal, because if a method has a high sensitivity value to changes in ranking, the method is increasingly chosen. Based on the black box testing that has been done, the results show that the functionality of the comparison application of the SAW and WP methods through a sensitivity test approach in evaluating employee performance at PT. Pelabuhan Indonesia II (Persero) Bengkulu Branch is running as expected and the application is able to display the results of the analysis of the SAW and WP methods and display the test results of the sensitivity test results.